Pengaruh Mobilisasi Dini Terhadap Tingkat Nyeri pada Pasien Post Sectio Caesarea (SC) dengan Metode Enhanced Recovery After Caesarian Surgery (ERACS) di Ruang Recovery Room (RR) RS Juliana Bogor: The Effect of Early Mobilization on Pain Levels in Post-Caesarean Section Patients Using the Enhanced Recovery After Caesarean Surgery (ERACS) Method in the Recovery Room at Juliana Hospital Bogor - Siti Kulsum; Lannasari; Nurul Ainul Shifa (MPI Press, 2025)
Introduction: Cesarean section is a method of delivery whereby the baby is removed through the mother's uterine wall via an incision in the abdomen and uterus. Post-cesarean section patients usually experience post-operative pain, which can cause discomfort. To overcome this problem, early mobilization can be performed, which not only reduces pain but also increases patient independence. Objectives: This study aims to identify the effect of early mobilization on pain levels in post SC patients using the ERACS method Method: The research design used quantitative experimental research (Quasi-Experiment) and employed a One-Group Pretest-Posttest Design approach. The research was conducted in July 2025. The research sample consisted of 20 patients using research instruments such as observation sheets, NRS sheets, and ERACS early mobilization SOPs after SC. Data analysis was performed using the Wilcoxon test Result: The Wilcoxon test showed that there was a significant effect with a p-value of 0.005. This means that the p-value was <0.05 for the variable of pain level before early mobilization and pain level after early mobilization Conclusion: Based on this study, early mobilization can affect the pain level of post-SC patients using the ERACS method. It is hoped that the early mobilization SOP after SC using the ERACS method can be used and applied to reduce the pain experienced by patients.